2016
DOI: 10.2147/ott.s92707
|View full text |Cite
|
Sign up to set email alerts
|

Radix Tetrastigma hemsleyani flavone inhibits proliferation, migration, and invasion of human lung carcinoma A549 cells

Abstract: Radix Tetrastigma hemsleyani flavone (RTHF) is widely used as a traditional herb and has detoxification and anti-inflammatory effects. In this study, we investigated the potential effects of RTHF on the growth and metastasis of human lung adenocarcinoma A549 cells and evaluated its mechanisms. A549 cells were treated with RTHF at various concentrations for different periods. In vitro Cell Counting Kit-8 assay and colony formation methods showed that RTHF had dose- and time-dependent antiproliferation effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Furthermore, they explored and found that RTHF exhibited anti-growth and antimetastasis activity in lung cancer A549 cells by regulating the expression of MMPs and tissue inhibitors of metalloproetienases. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they explored and found that RTHF exhibited anti-growth and antimetastasis activity in lung cancer A549 cells by regulating the expression of MMPs and tissue inhibitors of metalloproetienases. 22 …”
Section: Discussionmentioning
confidence: 99%
“…In the in vitro experiments with different lung cancer cells (A549 cells and A431 cells), the total flavonoids of TDG can inhibit the proliferation and apoptosis of tumor cells, and its mechanism of action involves the Bcl-2 family proteins, Caspase family proteins, MAPK pathway, and the ubiquitin-proteasome pathway. Besides, the total flavonoids of TDG can markedly inhibit the metastasis and invasion of tumor cells, with migration and invasion being associated with the activation of MMPs and TIMPs proteins (Zhong et al, 2013;Zhong et al, 2016;Zhong et al, 2017;Zhong et al, 2019). The above studies indicate that the total flavonoids of TDG has a very good therapeutic effect on lung cancer at the cellular level.…”
Section: Pharmacological Activities Anti-tumor Activitymentioning
confidence: 93%
“…Clinical studies have shown that flavonoids may have great implications in the prevention and treatment of cancer in humans 6,7. Component analyses showed that RTH is rich in flavones, and RTH flavone (RTHF) has good in vivo and in vitro effects on various cancers, including lung cancer 8,9. However, its antitumor mechanism and related regulatory pathway are still uncertain.…”
Section: Introductionmentioning
confidence: 99%